Luminally Acting Agents for Constipation Treatment: A Review Based on Literatures and Patents - Yang, Hong; Ma, Tonghui (Frontiers in Pharmacology, 2017)
Constipation is one of the most frequently reported gastrointestinal (GI) disorders that negatively impacts quality of life and is associated with a significant economic burden to the patients and society. Traditional treatments including lifestyle modification and laxatives are often ineffective in the more severe forms of constipation and over the long term. New medications targeting at intestinal chloride channels and colonic serotonin receptors have been demonstrated effective in recent years. Emerging agents focusing on improving intestinal secretion and/or colonic motility have been shown effective in animal models and even in clinical trials. Recognization of the role of cystic fibrosis transmembrane regulator (CFTR) and calcium-activated chloride channels (CaCCs) in intestine fluid secretion and motility modulation makes CFTR and CaCCs promising molecule targets for anti-constipation therapy. Although there are multiple choices for constipation treatment, there is still a recognized need for new medications in anti-constipation therapy. The present review covers the discovery of luminally acting agents for constipation treatment described in both patents (2011-present) and scientific literatures.